Rooftop PV System Policy and Implementation Study for a Household in Indonesia - Tarigan, Elieser (International Journal of Energy Economics and Policy, 2020)
This paper discusses the recent solar rooftop PV system policies in Indonesia, particularly for the implementation of the residential sector. The aim of this study is to demonstrate the rooftop PV system for a household based on the current related policies. The study is conducted by literature reviews and computer simulation for a typical rooftop PV system for residential in Surabaya, Indonesia. The most recent solar energy policy in Indonesia is the Ministry of Energy and Mineral Resources (MEMR) Regulation No. 49, the year 2018, which establishes net metering for the residential, commercial and industrial National Grid (PLN) customers that have excess power from solar rooftop installations. The simulation shows the average values global solar irradiation on a horizontal surface in Surabaya vary between 6.81 kWh/m2 and 4.82 kWh/m2 with an average of 5.54 kWh/m2 per day. Energy output by 3 kWp rooftop PV system in Surabaya is found about 4,200 kWh per year, with an average of 11.67 kWh/day. Economically, under present conditions, rooftop on-grid PV system investment would give about 9-10 years of the payback period. Keywords: Rooftop, PV System, Solar Energy, Residential, Indonesia JEL Classifications: C58, G18, H41,H50 & Z18 DOI: https://doi.org/10.32479/ijeep.9539